An ordered array of hierarchical spheres for surface-enhanced Raman scattering detection of traces of pesticide. (16th August 2016) - Hu, Xiaoye; Zheng, Peng; Meng, Guowen; Huang, Qing; Zhu, Chuhong; Han, Fangming; Huang, Zhulin; Li, Zhongbo; Wang, Zhaoming; Wu, Nianqiang
Abstract: An ordered array of hierarchically-structured core-nanosphere@space-layer@shell-nanoparticles has been fabricated for surface-enhanced Raman scattering (SERS) detection. To fabricate this hierarchically-structured chip, a long-range ordered array of Au/Ag-nanospheres is first patterned in the nano-bowls on the planar surface of ordered nanoporous anodic titanium oxide template. A ultra-thin alumina middle space-layer is then conformally coated on the Au/Ag-nanospheres, and Ag-nanoparticles are finally deposited on the surface of the alumina space-layer to form an ordered array of Au/Ag-nanosphere@Al2 O3 -layer@Ag-nanoparticles. Finite-difference time-domain simulation shows that SERS hot spots are created between the neighboring Ag-nanoparticles. The ordered array of hierarchical nanostructures is used as the SERS-substrate for a trial detection of methyl parathion (a pesticide) in water and a limit of detection of 1 nM is reached, indicating its promising potential in rapid monitoring of organic pollutants in aquatic environment.